Effect of Oat flour on Quality Characteristics of Low-Fat Chicken Sausages - Reddy, G.V. Bhaskar; Kumar, M. Shashi; Gupta, R.S.D.; Kiran, M.; Reddy , K. Kondal (Journal of Meat Science, 2012)
This study was conducted to evaluate the influence of adding oat flour at various levels i.e. 3, 6 and 9 per cent on physico-chemical, proximate, textural and sensory attributes of low-fat chicken sausages as compared to 9 per cent ground nut oil control sausages. Significant (P < 0.05) improvements in cooking yield, emulsion stability, water-holding capacity, pH were noticed and low fat chicken sausages incorporated with 9 per cent oat flour had recorded significantly (P<0.05) highest values compared to control and other level of oat flour extension. Addition of oat flour significantly (P<0.05) increased moisture, fat and crude fibre, moisture and fat retention values compared to control. Because of larger moisture absorption and moisture retention during cooking properties of oat soluble fibre maintains the textural integrity of the sausages without fat addition. Addition of oat flour increased the crude fibre content of low fat chicken sausages. Hardness values are significantly (P<0.05) reduced as the level of oat flour increased due to highest water retention of oat flour added sausages. In sensory attributes i.e. colour, juiciness, tenderness and overall acceptability of low-fat chicken sausages were found to be highest in oat flour added sausages compared to control. From the results obtained in this study, it can be concluded that oat flour can be used successfully as a fat substitute in low-fat chicken sausages without deteriorating the product quality.